Menstrual health and period poverty in Lebanon during economic crisis: A qualitative analysis of the challenges and recommendations - Elhage Hassan, Malika; Doumat, George; Daher, Darine; Al Tannir, Abdul Hafiz; Hassan, Bashar; Chidiac, Charbel; Hariri, Hussein; Hatab, Taha; Abou Daher, Alaa; Ezzedin, Omar; Fouad, Fouad M. (Frontiers in Reproductive Health, 2022)
Objective Recently, severe period poverty has had a dramatic spread throughout Lebanon as a result of several crises: the COVID-19 pandemic, the Beirut explosion, and the economic collapse. Period poverty is the lack of access to menstrual hygiene materials, comfortable environments, and adequate education about menstrual health. Due to the great implications of period poverty on Lebanese women's health, our study aims to explore stakeholder's perspective on the Lebanese public health policy regarding menstrual health, the evolving challenges it faces in the context of the current economic collapse, and to suggest recommendations for solutions. Methods Our study is qualitative in nature, where data collection was done via online semi-structured interviews with stakeholders from the public and private sectors of the Lebanese healthcare system in addition to non-governmental organizations (NGOs) and physicians. Data were then analyzed based on themes and subthemes that emerged from the interviews. Results Nine stakeholders were interviewed: five from NGOs, two obstetrics and gynecology physicians, and two public sector representatives. The challenges to menstrual health were subcategorized into previously existing and new ones. The consequences of poor menstrual health were tackled on the mental, physical, and social levels. Stakeholders suggested both short-term and long-term recommendations. Short-term recommendations included decreasing the monetary burden by subsidizing menstrual products or via a coupon system. Long-term recommendations included proper education on multiple levels, cooperation between key players in the private and public sectors, and encouragement of local production to ensure future sustainability. Conclusion Menstrual health is a neglected public health issue in Lebanon, causing detrimental effects on girls and women residing in the country. Proper planning and collaboration between the private and public sectors are required to address this human rights issue.